(untitled) (Global Journal of Science Frontier Research, 2014)
The synthesis of ZnO nanoparticles has attracted considerable interest because of their unique properties and potential applications in a variety of solid state devices, catalytic media etc. By using water-in-oil (w/o) microemulsions, nanodroplets of water were used as chemical reactor to synthesize nanoparticles of zinc oxide. Addition of reducing agent ((NH 4 ) 2 CO 3 ) and zinc salt (Zn(NO 3 ) 2 ) followed by heat treatment results in the formation of zinc oxide nanoparticles (NPs). The structural and optical properties of the samples were investigated by X-ray diffraction and UV-VIS-NIR absorption spectroscopy. X-ray diffraction revealed the wurtzite structure of ZnO. Percentage of lattice contraction and average particle size of the sample were also calculated from the XRD. Size-dependent blue shifts of absorption spectra revealed the quantum confinement effect. Furthermore, on increasing annealing temperature of ZnO NPs, crystallize size increases which, in turn,decreases the band gap energy and photocatalytic degradation efficiency of phenol.